2007
DOI: 10.1016/j.otohns.2007.02.037
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Thyroid Carcinoma in Fluorodeoxyglucose Positron Emission Tomography‐Positive Thyroid Incidentalomas

Abstract: Our experience shows a 14% malignancy rate for the dominant (imaged) nodule and a total malignancy rate of 32% when the incidental micro carcinomas are included. Both of these rates are significantly lower than results published previously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
51
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 13 publications
7
51
1
2
Order By: Relevance
“…The significance of incidental focal thyroid uptake on 18 F-FDG PET study was first described in 2001 [10]. Many research studies are currently available on this topic, with different results on focal uptake of tracer on 18 F-FDG PET [3,4,5,6,8,9,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38]; however, a large UK series has yet to be reported. We report one of the largest studies on the evaluation of incidental focal 18 F-FDG uptake in the thyroid.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of incidental focal thyroid uptake on 18 F-FDG PET study was first described in 2001 [10]. Many research studies are currently available on this topic, with different results on focal uptake of tracer on 18 F-FDG PET [3,4,5,6,8,9,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38]; however, a large UK series has yet to be reported. We report one of the largest studies on the evaluation of incidental focal 18 F-FDG uptake in the thyroid.…”
Section: Discussionmentioning
confidence: 99%
“…Still, its presence can be problematic in some cases, particularly if the quality of morphologic images is impaired by motion In the thyroid, focal tracer uptake is problematic. Although Choi et al (28) found increased focal tracer uptake to be a strong predictor for malignancy, more recent studies showed that also benign nodules show a strong tracer uptake and that the frequency of malignant nodules is lower than initially reported (29). Still, focal asymmetrical 18 F-FDG uptake in the thyroid demands further investigation (25,29,30).…”
Section: Discussionmentioning
confidence: 93%
“…Although Choi et al (28) found increased focal tracer uptake to be a strong predictor for malignancy, more recent studies showed that also benign nodules show a strong tracer uptake and that the frequency of malignant nodules is lower than initially reported (29). Still, focal asymmetrical 18 F-FDG uptake in the thyroid demands further investigation (25,29,30). Unfortunately, MRI is not superior to CT in the differentiation between benign and malignant thyroid lesions (31).…”
Section: Discussionmentioning
confidence: 97%
“…al [1] article with great interest as we have pursued this topic in our center over the years [2][3][4]. We practice at a busy international multiple myeloma referral center so we have a busy nuclear medicine/ PET practice with abundant PET data.…”
mentioning
confidence: 99%
“…Diffuse thyroid uptake on PET/CT is not a concern for malignancy and is indicative of thyroid disease which may ultimately require medical management [2].…”
mentioning
confidence: 99%